PKC gamma senses/protects from stress in retina through regulation of gap junctions - Yevseyenkov, Vladimir (Kansas State University, 2010)
Exposure to oxidative stress leads to accumulation of reactive oxygen species and this stimulates protective cellular functions as a compensatory response to prevent the spread of apoptotic signal and prevent cell death. The purpose of this dissertation is to understand the importance of PKCγ activation and regulation of the retinal gap junction protein Cx50, and what role PKCγ plays in this neuro-protective effect. Through electron microscopy we were able to show that PKCγ knockout mice retinas had incomplete cellular organization in the outer plexiform layer (OPL) of the retina, the layer of retina where Cx50 plays an important role in retinal cellular synapses. Electroretinograms confirmed that this structural disorganization also led to loss of functional response to light stimuli in PKCγ knockout mice retinas. In vivo exposure to 100% hyperbaric oxygen (HBO) caused significant degradation of the retina in knockout mice compared to control mice. Thicknesses of the inner and nuclear and ganglion cell layers were increased, with complete disruption of OPL in PKCγ KO mice retinas. Damage to the outer segments of the photoreceptor layer and ganglion cell layer was significantly more apparent in the central retinas of HBO-treated knockout mice. Cx50 immunolabeling showed significant reduction to HBO treatment of PKCγ control mice retinas, HBO treatment failed to produce reduction of Cx50 immunolabeling in KO mice retinas. In the R28 retinal cell line, PKCγ enzyme was shown to be activated by phorbol ester (TPA) and hydrogen peroxide. This resulted in translocation to the cellular membrane as confirmed by western blot and confocal microscopy. Suppression of PKCγ by siRNA rendered R28 cells more sensitive to oxidative stress-induced cell apoptosis, the process of apoptosis started earlier, and this resulted in cell death. R28 treatment with phorbol esters and hydrogen peroxide led to reduction in gap junction activity and Cx50 gap junction cell disassembly. This dissertation shows that PKCγ plays an important role in structural organization of retina and has a neuro-protective effect in response to oxidative stress, in part because of its control of Cx50.
Keywords: Protein Kinase C gamma; Retina; Oxidative Stress; Gap Junctions; Chemistry, Biochemistry (0487)